1995
DOI: 10.1103/physrevlett.75.1691
|View full text |Cite
|
Sign up to set email alerts
|

Reentrance Phenomena in Noise Induced Transitions

Abstract: We analyze a model that has been shown to undergo a purely noise induced transition, from a monostable regime to a bistable one, when it is submitted to a white or colored noise source. We show, using a consistent interpolating Markovian approximation for the colored noise case, that for large values of the correlation time, the system undergoes a new transition to a monostable state, indicating a reentrancelike phenomenon in its phase diagram. Numerical results support our findings. PACS numbers: 05.40.+j The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 15 publications
5
57
0
Order By: Relevance
“…The reentrance phenomenon was firstly observed in an analysis of a chemical reaction system driven by one colored noise, which showed that the system undergoes a purely noiseinduced transition from a monostable regime to a bistable one, then to the monostable regime as the noise correlation time increases [2]. This phenomenon has also been found in a bistable system subjected to the cross-correlated noises [10].…”
Section: Introductionmentioning
confidence: 95%
“…The reentrance phenomenon was firstly observed in an analysis of a chemical reaction system driven by one colored noise, which showed that the system undergoes a purely noiseinduced transition from a monostable regime to a bistable one, then to the monostable regime as the noise correlation time increases [2]. This phenomenon has also been found in a bistable system subjected to the cross-correlated noises [10].…”
Section: Introductionmentioning
confidence: 95%
“…Studies have confirmed the role of noise in nonlinear stochastic systems [1]. Now it has been realized that the effects of noise have widely appeared in all kinds of nonlinear systems including bistable systems [2][3][4][5], laser systems [6,7] and biological systems [8][9][10][11][12]. Some of the notable examples of noise induced effects are stochastic resonance in biological systems.…”
Section: Introductionmentioning
confidence: 95%
“…We believe that this will be a general behavior for long tail (power-law) and cut-off noise distributions, respectively. A closer look shows the persistence of the reentrance effect previously found in [13]: for some fixed values of the noise intensity D it is possible to obtain a transition, first from unimodal to bimodal and then back to unimodal, just by varying the time correlation τ of the noise.…”
Section: Non-gaussian Noise and Its Propertiesmentioning
confidence: 99%
“…In Ref. [13] the effect of a colored Gaussian (Ornstein-Uhlenbeck) noise on that model was analyzed in detail and a novel reentrance phenomenon in the phase diagram was found. In order to study the effect that the non-Gaussian nature of the noise can have in the transition, we have used here a particular distribution [14] whose departure from the Gaussian behavior is governed by a parameter q: while q = 1 corresponds to Gaussian noise, the value q > 1 produces a long tail distribution and q < 1 gives a cut-off distribution.…”
Section: Introductionmentioning
confidence: 99%